ANALISIS GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM RESTRUKTURISASI DI SEKOLAH INKLUSIF CHERISH ACADEMY - Handayani, Siti; Murniarti, Erni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The quality of school leadership, which influences the effectiveness of learning, teacher performance, and student motivation to achieve, is crucial. A principal with strong managerial and leadership skills will be able to translate the school's vision and mission into numerous well-planned and measurable strategic programs, thereby sustainably improving the quality of education. This study aims to specifically analyze the principal's leadership style in the organizational and learning restructuring process at the Cherish Academy Inclusive School. The restructuring was carried out in response to the increasing diversity of student needs, especially students with special needs, as well as demands for improving the quality of inclusive education services. This study used a qualitative approach with a case study method, which allows for in-depth data collection on the principal's leadership practices in managing structural and cultural changes in the school environment. The results show that the principal applies a transformational-participatory leadership style characterized by teacher involvement in decision-making, intensive mentoring in the implementation of inclusive learning, and open communication during the restructuring process. The restructuring focused on structuring teacher work structures, strengthening collaboration between classroom teachers and special needs teachers, and adjusting learning policies oriented to individual student needs.